OBSERVATION OF CHILDREN EXPERIENCED MENINGOCOCCAL INFECTION - O.A. Rychkova; E.A. Kashuba; T.G. Drozdova; A.A. Bel’tikova (Вопросы современной педиатрии, 2010)
(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(3):156-157)